2020
DOI: 10.52547/archhygsci.9.4.299
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Pollution in Surface Soils of Ahvaz, Iran, Using Pollution Indicators and Health Risk Assessment

Abstract: Background & Aims of the Study: Heavy metals are among the most dangerous environmental pollutants entering the air, water, and soil through human and natural activities with the potential of poisoning, pathogenicity, and carcinogenicity to living organisms and humans. The current study aimed to determine the contamination of heavy metals, including lead, zinc, copper, arsenic, chromium, and cadmium, in the surface soils of Ahvaz, Iran, using pollution indicators and health risk assessment. Materials and Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 27 publications
(31 reference statements)
0
13
0
Order By: Relevance
“…A research reported that accumulation of PTEs in the surface soils of Ahvaz was Cu > Pb > Cr > Zn > As > Cd and the high concentrations in addition to a high coefficient of variation indicated the human role for toxic metals. 26 Guan et al investigated the amount of PTEs in an industrial and mining area called Tianjin in China. They found that the highest levels of contamination in the study area were related to Zn, and the contamination of Cu, Cd and Pb was higher than average earth's crust.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A research reported that accumulation of PTEs in the surface soils of Ahvaz was Cu > Pb > Cr > Zn > As > Cd and the high concentrations in addition to a high coefficient of variation indicated the human role for toxic metals. 26 Guan et al investigated the amount of PTEs in an industrial and mining area called Tianjin in China. They found that the highest levels of contamination in the study area were related to Zn, and the contamination of Cu, Cd and Pb was higher than average earth's crust.…”
Section: Resultsmentioning
confidence: 99%
“…43,44 The average concentrations of arsenic, cadmium, chromium, copper, lead and zinc in the soils of Eghlid city in southern Iran were 45 Many studies have showed that the concentration of heavy metals in topsoil can vary. 10,11,16,26,45 This difference in concentration of heavy metals may be due to human activities such as industry, agriculture and urbanization. However, the geological processes of the region can also affect the concentration of heavy metals in the soil.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the equation, Cn represents the concentration of each element in the sediment, and Co is the average concentration of each element in the shale ( Supplementary Table S1 ) ( 49 , 50 ).…”
Section: Methodsmentioning
confidence: 99%